Structural Brain Lesions and Gait Pathology in Children With Spastic Cerebral Palsy - Papageorgiou, Eirini; De Beukelaer, Nathalie; Simon-Martinez, Cristina; Mailleux, Lisa; Van Campenhout, Anja; Desloovere, Kaat; Ortibus, Els (Frontiers in Human Neuroscience, 2020)
The interaction between brain damage and motor function is not yet fully understood in children with spastic cerebral palsy (CP). Therefore, a semi-quantitative MRI (sqMRI) scale was used to explore whether identified brain lesions related to functional abilities and gait pathology in this population. A retrospective cohort of ambulatory children with spastic CP was selected (N=104; 52 bilateral (bCP) and 52 unilateral (uCP)). Extent and location-specific scores were defined according to the sqMRI scale guidelines. The gross motor function classification system (GMFCS), the gait profile score (GPS), GPSs per motion plane, gait variable scores (GVS) and multiple-joint (MJ) gait patterns were related to brain lesion scores. In all groups, the global total brain scores correlated to the GPS (total: rs=0.404, p≤0.001; bCP: rs=0.335, p≤0.05; uCP: rs=0.493, p≤0.001). The global total hemispheric scores correlated to the GMFCS (total: rs=0.392, p≤0.001; bCP: rs=0.316, p≤0.05; uCP: rs=0.331, p≤0.05). The laterality scores of the hemispheres in the total group correlated negatively to the GMFCS level (rs=-0.523, p≤0.001) and the GVS-knee sagittal (rs=-0.311, p≤0.01). Lesion location, for the total group demonstrated positive correlations between parietal lobe involvement and the GPS (rs=0.321, p≤0.001) and between periventricular layer damage and the GMFCS (rs=0.348, p≤0.001). Involvement of the anterior part of the corpus callosum (CC) was associated with the GVS-hip sagittal in all groups (total: rpb=0.495, p≤0.001; bCP: rpb=0.357, p≤0.05; uCP: rpb=0.641, p≤0.001). The global total hemispheric and laterality of the hemispheres scores differentiated between the minor and both the extension (p≤0.001 and p≤0.001) and flexion (p=0.016 and p=0.013, respectively) MJ patterns in the total group. Maximal periventricular involvement and CC intactness were associated with extension patterns (p≤0.05 and p≤0.001, respectively). Current findings demonstrated relationships between brain structure and motor function as well as pathological gait, in this cohort of children with CP. These results might facilitate the timely identification of gait pathology and, ultimately, guide individualized treatment planning of gait impairments in children with CP.